Study of Fibrinogen Level in Acute Ischemic Stroke Patients in Medical Intensive Care Unit - Ghada M. Samir; Osama A. Khalil; Mohamed S. Fawzy; Ayman M. E. M. Sadek (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Stroke is one of the most common causes of morbidity and mortality worldwide. Stroke patients with higher plasma fibrinogen level have an increased risk for unfavorable functional outcome, short-term mortality, and new cardiovascular events. The aim of this study is to estimate fibrinogen levels in patients with acute ischemic stroke in the medical intensive care unit (ICU) and its relationship to other risk factors and outcome, seeking an efficient predictor. We conducted an observational cohort study in the medical ICU of Zagazig University. Materials and Methods Sixty-four ICU patients were divided into acute ischemic stroke patients (group I, n=32) and nonstroke patients (group II, n = 32). Full history, thorough clinical examination, routine investigations, Computed Tomography (CT) or Magnetic Resonance Imaging (MRI) brain, APACHE II score, and serum fibrinogen level were measured 48hours after admission. Results A significant increase in serum fibrinogen level was noticed in group I (P < .001) with a cutoff value ≥439mg/dL showed sensitivity 92.31%, specificity 75.36%, and accuracy 84.34% for stroke occurrence with area under the curve 0.86. A cutoff value ≥557 mg/dL showed sensitivity of 85.71%, specificity 96%, and an accuracy of 93.75% for mortality in this group with area under the curve 0.97. Only diabetes mellitus showed an impact on the in-hospital outcome (P = .04). Discussion High serum fibrinogen levels in high-risk individuals, especially the diabetics, may be used as a predictor for the occurrence of acute ischemic stroke and mortality from stroke.